A new species of Melanophryniscus (Anura, Bufonidae) from the Campos Gerais region of Southern Brazil - Steinbach-Padilha, Giovanna C. (Phyllomedusa: Journal of Herpetology, 2008)
A new species of Melanophryniscus is described from the Parque Estadual de Vila Velha, municipality of Ponta Grossa, Paraná State, Southern Brazil. The Parque Estadual de Vila Velha is located in the Campos Gerais region, an environment dominated by natural grasslands with patches of Araucaria Forest. The new species is distinguished from all congeners by its small size (12.8-14.0 mm snout-vent length in adult males) and unique color pattern of copper brown dorsum covered with small spinulose black warts; ventral surface black finely spotted with white, posterior abdomen and ventral surfaces of the forearm, hand and foot with red stains. The new species is nocturnal and breeds in the water accumulated in the leaf-axils of phytotelmata.